Identifikasi Senyawa Tanin Pada Ekstrak Sabut Buah Pinang (Areca catechu. L) - Rustiah, Waode; Muharram, A. Fatmawati; Arisanti, Dewi; Alfian, Alfian (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2021)
Areca catechu (Areca catechu. L) contains many chemical components, namely, pectin, cellulose, hemicellulose, lignin, pectin oxalate and flavonoids. Tannins are very complex organic substances and consist of phenolic compounds. Tannins are obtained by extraction with water and ethanol solvents because tannins can dissolve with these solvents. This study aims to identify tannin compounds in areca nut using ethanol as a solvent. This research is a laboratory experiment with an extraction process using the maceration method. The areca nut is dried and mashed and then sifted. Then the powder was macerated with 70% ethanol solvent for ± 24 hours, then evaporated and then tested qualitatively and determined the type of tannins. The results showed that areca nut extract was positive for tannins and the type of tannin was condensed tannins.